Exogenous Trehalose Improves Growth, Glycogen and Poly-3-Hydroxybutyrate (PHB) Contents in Photoautotrophically Grown Arthrospira platensis under Nitrogen Deprivation - Nat-Anong Mudtham; Authen Promariya; Chanchanok Duangsri; Cherdsak Maneeruttanarungroj; Suchanit Ngamkala; Nattaphong Akrimajirachoote; Sorawit Powtongsook; Tiina A. Salminen; Wuttinun Raksajit (Biology, 2024)
was confirmed by FTIR and NMR analysis. This research represents the first study examining the performance of trehalose in promoting glycogen and PHB production in cyanobacteria under nitrogen-deprived conditions.
Keywords: Algal biology and biofuel production; Biocrusts and Microbial Ecology; Aquatic Ecosystems and Phytoplankton Dynamics